CRIMINAL COURT SYSTEM FOR JUVENILE CRIMINAL OFFENDER IN INDONESIA AND THE STRUGGLE FOR ACCESS TO JUSTICE - Zenny Rezania Dewantary (President University, 2016)
The criminal law system of Indonesia formed a special court system for children criminals. This system is determined by considering that juvenile has distinguishing factors than adult that drive them to conduct criminality. Those can be analyzed based on psychological and sociological factors. The main purpose is to secure access for justice towards children criminality. However, provisions in Juvenile Court System law still have weaknesses that will endanger the access of justice. Therefore, in the enforcement aspects, that inclusivity is often being abandoned. This research is interdisciplinary by using normative-empirical method and qualitative method. Normative-empirical is analyzing on legal instrument using statute approach and also using primary data taken from interview. Qualitative method is a method that holistically describes a phenomenon by analyzing the quality of relations, situations, and other materials. This research analyzed on the inclusivity of juvenile delinquents that has affected the law making process by constituting special court system for children, then criticizing on how poor the law being constituted and then affecting the enforcement. Law enforcers have awareness on prioritizing restorative justice as mandated by the Law. But there is a structural problem among the realization of it. The law enforcement needs to be improved both in the substantial aspect and attributive aspect.